PEMBELAAN TERPAKSA DALAM DELIK PENGANIYAAN YANG MENYEBABKAN LUKA RINGAN (STUDI TERHADAP PUTUSAN PN PADANG NO, 372/PID.B/2020/PN.PDG) - Ahmad Yani Y Alhaddad; Rugun Romaida Hutabarat (Fakultas Hukum Universitas Tarumanagara, 2021)
Noodweer or self-defense is one of the reasons for eliminating crime and is described in Article 49 (1) of the Penal Code. The act committed is the basis of justification known as the basis of justification. That is, Apology can rule out the nature of the illegal act, and the act committed by the defendant may be correct. However, the problem with writing is that ES was attacked by AF and Eko should be considered a victim. However, in reality, the judge of Judgment No. 372 / Pid.B / 2020 / PN.Pdg accused Defendant ES in Article 351 (1). .. To complete this study, the author uses four theories: the theory of reasons for crime exclusion, the theory of criminal activity, the theory of criminal imposition, and the theory of judge authority. Court decision NP No. 372 / Pid.B / 2020 / Pn.Pdg stated that the defendant did not meet one of the conditions for compulsory defense and therefore did not prove to have taken compulsory defense under Article 49 (1). The defendant was found based on paragraph (1). Article 351 was condemned. Regarding tracking of identified items, such as (1) anyone, (2) items that are offensive or injured, (3) items that are intentionally worn.